COVID-19 Infection Risk and Depressive Symptoms Among Young Adults During Quarantine: The Moderating Role of Grit and Social Support - Hou, Jie; Yu, Qingyun; Lan, Xiaoyu (Frontiers in Psychology, 2021)
Prior research has demonstrated that the adverse consequences of the COVID-19 pandemic may go beyond its economic hardships and physical health concerns, having a significant influence on psychological distress for individuals under quarantine. Nevertheless, relatively little attention has been paid to exploring the risk and protective factors in the link between COVID-19 infection risk and psychological distress among young adults. Following a socioecological framework, the current study examines the moderating role of grit (perseverance and consistency) and social support in the association between COVID-19 infection risk and depressive symptoms. A sample of 1251 young adults under home quarantine (62.6% female; M age = 20.92 years, SD = 1.47; age ranged from 18 to 25 years old) was involved in this study, and they were asked to complete a set of self-reported questionnaires online. Results of a linear regression analysis exhibited that COVID-19 infection risk was positively associated with depressive symptoms in young adults in quarantine. Moreover, moderation analyses showed that this association was moderated by perseverance and social support. To be specific, for those reporting higher levels of social support, this linkage was not significantly positive; in contrast, for those reporting lower levels of social support, perseverance was a significant protective factor for depressive symptoms when young adults were exposed to high infection risk of COVID-19. The current study suggests that greater social support is essential to helping young adults deal with possible negative emotions in the context of the COVID-19 pandemic. Moreover, university-based counseling services should pay specific attention to those young adults with relatively insufficient social support resources and low levels of perseverance.